Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos (Journal of Development Effectiveness, 2021)
Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)’s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED’s programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.
Keywords: Cost effectiveness; Girls’ Education; Tanzania; equity

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

The relationship between educational television and mathematics capability in Tanzania - Watson, Joe; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2021)
Previous studies have often demonstrated that educational television can have a positive effect on learning outcomes in low-income countries when delivered in controlled settings. However, existing research in low-resource contexts has scarcely considered the association between child outcomes and viewing in usual environments (ie, at their home, a friend’s home or a relative’s home). This lack of research is striking, as evidence from controlled settings might provide limited information on the effects of normal television exposure. This paper, therefore, investigates the relationship between normal exposure to a popular Tanzania-produced cartoon, Ubongo Kids and mathematics capability, as represented by plausible values derived from an item response theory model applied to children’s test responses. Cross-sectional investigation of a sample of 38 682 Tanzanian children suggested normal educational television exposure to be significantly associated with mathematics capability, when controlling for age, sex, school enrolment, Kiswahili attainment and household fixed effects. While cross-sectional results are not necessarily causal, the findings in this paper broadly correspond with those from previous designs using repeated observations. What is more, considering association results alongside cost and viewership estimates suggests television-based interventions to be highly cost effective. Practitioner Notes What is already known about this topic National data for Tanzania suggests the country to have both low levels of mathematics proficiency and considerable access to television technology. Educational television-based interventions might, therefore, be worthy of consideration by educational policymakers, especially given that studies conducted in controlled settings indicate that television can deliver learning benefits. There is, however, little evidence concerning educational television exposure outside of controlled settings. Only one such study in a low-income context that concerned the association between learning outcomes and viewing among primary-age children has been identified. What this paper adds This paper addresses this dearth of research by investigating the association between normal exposure to a Tanzanian cartoon, Ubongo Kids and mathematics capability, as derived from an item response theory model applied to the test responses of 38 682 children. Cross-sectional findings suggest the association between normal television exposure and mathematics capability to be significant. Further, a cost-effectiveness comparison with alternate interventions in comparable contexts indicates that educational television is highly cost-effective. Implications for practice and/or policy The findings presented in this paper concerning educational television viewership in usual environments act to triangulate those from prior research conducted in controlled settings. As such, policymakers in low-income contexts now possess more convincing evidence on the potential influence of educational television interventions. Additionally, the cost-effectiveness comparison made suggests that educational television should be considered a viable option by policymakers seeking to address learning outcomes with limited resources.
Keywords: Tanzania; cost effectiveness; educational television; mathematics

Reimagining Girls' Education: Solutions to keep girls learning in emergencies - Guglielmi, Silvia; Jones, Nicola; Nicolai, Susan; Pereznieto, Paola; Plank, Georgia; Vu, Nhung; Sanchez-Tapia, Ingrid; Mackintosh, Alasdair (UNICEF, 2021)
Keywords: Access to Education; Barriers; Context Effect; Cost Effectiveness; Costs; Disadvantaged Youth; Distance Education; Educational Finance; Educational Technology; Emergency Programs; Equal Education; Evidence Based Practice; Females; Foreign Countries; Gender Bias; Inclusion; Intervention; Planning; Sex Fairness; Sex Stereotypes; Teaching Methods; Technology Uses in Education

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

Making the Grade: The Sensitivity of Education Program Effectiveness to Input Choices and Outcome Measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

Making the grade: The sensitivity of education program effectiveness to input choices and outcome measures - Kerwin, Jason T.; Thornton, Rebecca L. (The Review of Economics and Statistics, 2021)
This paper demonstrates the acute sensitivity of education program effectiveness to the choices of inputs and outcome measures, using a randomized evaluation of a mother-tongue literacy program. The program raises reading scores by 0.64 SD and writing scores by 0.45 SD. A reduced-cost version instead yields statistically insignificant reading gains and some large negative effects (−0.33 SDs) on advanced writing. We combine a conceptual model of education production with detailed classroom observations to examine the mechanisms driving the results; we show they could be driven by the program initially lowering productivity before raising it, and potentially by missing complementary inputs in the reduced-cost version.

EdTech and Covid-19: lessons from around the world - Pellini, Arnaldo (EdTech Hub, 2021)
Arnaldo Pellini, Susan Nicolai, Moizza Binat Sarwar, Sam Wilson, Akanksha Bapna, Chris McBurnie, Adedoyin Adesina, Oladele Akogun, Ernest Ngabo, Hind Al-Hindawi, Ni Wayan Suriastini, Vollan Ochieng, Moses Ngware, Asma Rabi , Abdul Musawir, Clement Sefa-Nyarko, Edem Agbe , Rabia Tabassum, Amna Zaidi, Jeroen Groenewegen, Harish Doraiswamy, Sudhansu Sharma, Liangdi Xu In this blog we summarise four takeaways from a reflection…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Abstract Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning

World Development Indicators - World Bank (2021)

Education Finance Watch 2021 - World Bank; UNESCO (Global Education Monitoring Report, 2021)

Unlocking Talent - Unlocking Talent (2021)

Research - EdTech Hub (EdTech Hub, 2021)

Teacher professional development in sub-Saharan Africa: Equity and scale - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (Embedding Social Justice in Teacher Education and Development in Africa, 2021)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: Author:Haßler; Björn-CV-OECS; _yl:a; dode_eth-src-dode; dode_eth-trf2-dode

Two-Thirds of Poorer Countries Are Cutting Education Budgets Due to COVID-19 - World Bank (World Bank, 2021)

Computer-assisted instruction tools: A model to guide use in low-and middle-income countries - Kaye, Thomas; Ehren, Melanie (International Journal of Education and Development using Information and Communication Technology, 2021)
Learning outcomes in low- and lower-middle-income countries (LMICs) require significant improvement. With traditional reform efforts taking many years to realise results, education practitioners in LMICs are searching for innovative ways to rapidly strengthen learning outcomes. One tool showing promise is computer-assisted instruction (CAI). While a growing number of studies document CAI’s positive impacts on learning outcomes, others have found nil or negative effects. Research has yet to identify why these differences occur, and, most importantly, which factors must be in place to ensure that CAI contributes to improving learning outcomes. The aim of our research was to fill this gap in the research by developing a model highlighting those factors influencing the results of CAI interventions. Adopting a realist-informed methodology, we analysed 21 resources shared by 13 experts from around the world. We used the results of this analysis to develop a model that outlines key trends that facilitate and/or impede the deployment of CAI tools in LMICs. We find that key factors that should be considered when designing CAI interventions include the operating environment; stakeholder engagement; infrastructure; technological trust; CAI tool design; content curation/creation; student engagement; classroom integration; teacher capacity; student capacity; and data collection and use. This model highlights both these individual elements as well as noting how these elements interact. The model provides a foundation that can guide future research in this under-examined area.
Keywords: ⛔ No DOI found

Makhalidwe Athu - Creative Association International (2021)

Makhalidwe Athu - Creative Association International (2021)

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

The global stakes of digitalization in education - Haßler, Björn (The global stakes of digitalization in education (Uganda), 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Determining the suitability of Whatsapp for Jusoor Azima Project - Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Child education in the time of pandemic: Learning loss and dropout - Khan, Muhammad Jehangir; Ahmed, Junaid (Children and Youth Services Review, 2021)
The disruptive effects of the COVID-19 pandemic had affected the education sector at an unprecedented scale. In order to contain the spread of the virus, a large number of countries across the globe have shut their schools to handle the pandemic. However, it has adversely affected students’ learning and school attendance. In this regard, we assess the impact of COVID-19 on the learning loss, school dropout, and the economic costs in term of foregone earnings for children in Pakistan. The study finds a substantial decrease in Learning Adjusted Years of Schooling (LAYS) with worsening consequences for girls than boys. Likewise, the aggregate economic cost amounts to 107 billion dollars when adjusted for human capital utilisation. Besides, our simulation results suggest that about 7.2 million children dropout due to a reduction in household expenditure by 50 percent. In comparison, the dropout is more pronounced at the primary level of schooling. The results recommend that the government design robust social protection and remote education strategies to mitigate school closure’s adverse effect on children’s learning. The emphasis should be rather on the long run strategies to cope with a resilient education system of futuristic orientation.

EdTech in developing countries: a review of the evidence - Rodriguez-Segura, Daniel (The World Bank Research Observer, 2021)
The emergence of educational technology (“EdTech”) in developing countries has been received as a promising avenue to address some of the most challenging policy questions within educational systems. In this paper, I review and synthesize all existing studies with credible causal identification frameworks of EdTech interventions in developing countries. While other studies review the evidence for EdTech interventions in developed countries, there is currently no equivalent study for developing contexts, in spite of the rising number of studies being produced. I classify studies into four thematic categories based on the type of EdTech intervention analyzed: Access to technology; technology-enabled behavioral interventions; improvements to instruction; and self-led learning. I find that EdTech interventions centered around self-led learning and improvements to instruction are the most effective forms of EdTech at raising learning outcomes. Similarly, technology-enabled behavioral interventions are less promising for generating large effects but highly cost-effective given their typically low marginal costs. Although expanding access to technology alone is not sufficient to improve learning, it is a necessary first step for some other types of interventions. More broadly, the overall success of interventions rests on the thoughtful customization of the EdTech solution to the policy constraints at hand. Finally, EdTech interventions across all thematic areas can and should act as complements by leveraging their respective comparative advantages to address deficiencies within educational systems in developing countries.

Child education in the time of pandemic: Learning loss and dropout - Khan, Muhammad Jehangir; Ahmed, Junaid (Children and Youth Services Review, 2021)
The disruptive effects of the COVID-19 pandemic had affected the education sector at an unprecedented scale. In order to contain the spread of the virus, a large number of countries across the globe have shut their schools to handle the pandemic. However, it has adversely affected students' learning and school attendance. In this regard, we assess the impact of COVID-19 on the learning loss, school dropout, and the economic costs in term of foregone earnings for children in Pakistan. The study finds a substantial decrease in Learning Adjusted Years of Schooling (LAYS) with worsening consequences for girls than boys. Likewise, the aggregate economic cost amounts to 107 billion dollars when adjusted for human capital utilisation. Besides, our simulation results suggest that about 7.2 million children dropout due to a reduction in household expenditure by 50 percent. In comparison, the dropout is more pronounced at the primary level of schooling. The results recommend that the government design robust social protection and remote education strategies to mitigate school closure’s adverse effect on children's learning. The emphasis should be rather on the long run strategies to cope with a resilient education system of futuristic orientation. (PsycInfo Database Record (c) 2021 APA, all rights reserved)
Keywords: Adjustment; COVID-19; Education; Learning Strategies; Learning loss; Pakistan; Pandemics; School Dropout; School Dropouts; School Learning

Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery - Angrist, Noam; de Barros, Andreas; Bhula, Radhika; Chakera, Shiraz; Cummiskey, Chris; DeStefano, Joseph; Floretta, John; Kaffenberger, Michelle; Piper, Benjamin; Stern, Jonathan (International Journal of Educational Development, 2021)
We model learning losses due to the COVID-19 pandemic and the potential for cost-effective strategies to build back better. Data from Early Grade Reading Assessments in Ethiopia, Kenya, Liberia, Tanzania, and Uganda suggest half to over a year’s worth of learning loss. In modeling losses over time, we found that learning deficits for a child in grade 3 could lead to 2.8 years of lost learning by grade 10. While COVID-19 has stymied learning, bold, learning-focused reform consistent with the literature reviewed in this paper—specifically reform on targeted instruction and structured pedagogy—could improve learning even beyond pre-COVID-19 levels.
Keywords: COVID-19; Education; Foundational skills; Learning loss; Recovery

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Large Learning Gains in Pockets of Extreme Poverty: Experimental Evidence from Guinea Bissau - Fazzio, Ila; Eble, Alex; Lumsdaine, Robin L; Boone, Peter; Bouy, Baboucarr; Hsieh, Pei-Tseng Jenny; Jayanty, Chitra; Johnson, Simon; Silva, Ana Filipa (2021)
Children in many extremely poor, remote regions are growing up illiterate and innumerate despite high reported school enrollment ratios. Possible explanations for such poor outcomes include demand – for example, low perceived returns to education compared to opportunity cost; and supply – poor state provision and inability of parents to coordinate and finance better schooling. We conducted a cluster-randomized trial in rural Guinea Bissau to understand the effectiveness and cost of concerted supply-based interventions in such contexts. Our intervention created simple schools offering four years of education to primary-school aged children in lieu of the government. At endline, children receiving the intervention scored 58.1 percentage points better than controls on early grade reading and math tests, demonstrating that the intervention taught children to read and perform basic arithmetic, from a counterfactual condition of very high illiteracy. Our results provide evidence that particularly needy areas may require more concerted, dramatic interventions in education than those usually considered, but that such interventions hold great potential for increasing education levels among the world’s poorest people.

Remote Learning: Evidence from Nepal during COVID-19 - Radhakrishnan, Karthika; Sabarwal, Shwetlena; Sharma, Uttam; Cullen, Claire; Crossley, Colin; Letsomo, Thato; Angrist, Noam (World Bank, 2021)
This note discusses early results from a distance education program on foundational numeracy for primary school students in Nepal during Coronavirus (COVID-19) evaluated in a randomized trial. The trial included 3,700 households with children in public school (grades 3-5). It provided support for foundational numeracy through mobile phone-based tutoring. The trial tested delivery through public school teachers and also through NGO facilitators. It led to a 30 percent increase in foundational numeracy, with teachers being slightly more effective at producing learning gains than NGO facilitators. These results suggest that instructional support through mobile phones can be a high-access and low-cost approach to providing instruction at scale
Keywords: Coronavirus; Covid-19; Numeracy; Pandemic Impact; Remote Learning; School Closure

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Short and Long-Run Distributional Impacts of COVID-19 in Latin America - Lustig, Nora; Martinez Pabon, Valentina; Neidhöfer, Guido (2021)
We simulate the short- and long-term distributional consequences of COVID-19 in the four largest Latin American economies: Argentina, Brazil, Colombia and Mexico. We show that the shortterm impact on income inequality and poverty can be very significant, but that additional spending on social assistance more than offsets the effect in Brazil. The offsetting effect is significant in Argentina and Colombia, and nil in Mexico where there has been no such expansion. We find that a universal basic income that would have produced the same reduction in the poverty gap as actual policies would have cost slightly more but would have benefited the poor (the nonpoor) slightly less (more). To project the long-term consequences, we estimate the impact of the pandemic on school achievement and its intergenerational persistence. We use information on school closures, educational mitigation policies, and account for educational losses related to health shocks and parental job loss. Our findings show that in all four countries the impact is strongly asymmetric and affects particularly the high-school completion rates of children from disadvantaged families. Our simulations suggest that mitigation policies seem to have a minor impact on containing these negative effects.

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

The last mile in school access: Mapping education deserts in developing countries - Rodriguez-Segura, Daniel; Kim, Brian Heseung (Development Engineering, 2021)
With recent advances in high-resolution satellite imagery and machine vision algorithms, fine-grain geospatial data on population are now widely available: kilometer-by-kilometer, worldwide. In this paper, we showcase how researchers and policymakers in developing countries can leverage these novel data to precisely identify “education deserts” – localized areas where families lack physical access to education – at unprecedented scale, detail, and cost-effectiveness. We demonstrate how these analyses could valuably inform educational access initiatives like school construction and transportation investments, and outline a variety of analytic extensions to gain deeper insight into the state of school access across a given country. We conduct a proof-of-concept analysis in the context of Guatemala, which has historically struggled with educational access, as a demonstration of the utility, viability, and flexibility of our proposed approach. We find that the vast majority of Guatemalan population lives within 3 km of a public primary school, indicating a generally low incidence of distance as a barrier to education in that context. However, we still identify concentrated pockets of population for whom the distance to school remains prohibitive, revealing important geographic variation within the strong country-wide average. Finally, we show how even a small number of optimally-placed schools in these areas, using a simple algorithm we develop, could substantially reduce the incidence of education deserts in this context. We make our entire codebase available to the public – fully free, open-source, heavily documented, and designed for broad use – allowing analysts across contexts to easily replicate our proposed analyses for other countries, educational levels, and public goods more generally.
Keywords: Access to education; Education deserts; Education in developing countries; School placement

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen